NHANES-based assessment of neutrophil-percentage-to-albumin and neutrophil-to-lymphocyte ratios as moderate predictors of mortality in adults with chronic respiratory diseases - Xu, Feng; Jiang, Pan (Frontiers in Pharmacology, 2025)
ObjectiveThis study aimed to evaluate the predictive roles of hematologic inflammatory biomarkers, including the neutrophil-percentage-to-albumin ratio (NPAR), neutrophil-to-lymphocyte ratio (NLR), and eosinophil-to-lymphocyte ratio (ELR), in relation to mortality among individuals with chronic respiratory diseases (CRDs).MethodsWe analyzed data from the National Health and Nutrition Examination Survey (NHANES) to assess the relationship between these inflammatory biomarkers and mortality in adults with CRDs. Multivariable Cox regression models were used to estimate hazard ratios (HRs) for all-cause mortality, adjusting for potential confounders. Receiver operating characteristic (ROC) curve analysis was employed to evaluate the predictive performance of these biomarkers, with the area under the curve (AUC) used to compare their accuracy.ResultsA total of 8,387 participants with CRDs were included in the analysis. Higher levels of NPAR were significantly associated with increased all-cause mortality (HR = 1.33, 95% CI: 1.26–1.40, P < 0.001). Similarly, elevated NLR was associated with higher mortality risk (HR = 1.24, 95% CI: 1.17–1.30, P < 0.001). In contrast, ELR did not show a significant association with mortality (HR = 1.04, 95% CI: 0.99–1.10, P = 0.098). ROC curve analysis revealed that NPAR had the highest AUC value (0.639, 95% CI: 0.623–0.656), suggesting modest yet relatively better discriminative capacity among the evaluated biomarkers for mortality risk stratification.ConclusionAmong individuals with chronic respiratory diseases, higher NPAR and NLR are significant predictors of mortality, with statistically significant but moderate predictive ability as indicated by their AUC values. These findings suggest that NPAR and NLR may serve as useful biomarkers for risk stratification in patients with CRDs, though their clinical utility is limited by modest predictive power.